2004
DOI: 10.1063/1.1643531
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive quartz crystal microbalance with porous gold electrodes

Abstract: Articles you may be interested inEffects of compressional waves on the response of quartz crystal microbalance in contact with silicone oil droplets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 10 publications
1
66
0
Order By: Relevance
“…This type of sequential competitive adsorption to artificial surfaces (Vroman et al, 1980) is now known as the Vroman effect and causes a more elastic or more firmly bound protein layer at the surface. The difference between f response of the harmonics considered may stem from the fact that the penetration depth decreases with the increase in operating frequency of the sensor (Cote et al, 2003;Hieda et al, 2004). Our results indicated that the sensor response to Stage-1 is primarily due to platelet binding to both collagen and to pre-absorbed protein layers, and that the TSM sensor operating at 35 MHz is more sensitive to the molecular interactions such as the Vroman effect occurring in very close proximity to the sensor surface, compared to operating at 5 MHz.…”
Section: Discussionmentioning
confidence: 99%
“…This type of sequential competitive adsorption to artificial surfaces (Vroman et al, 1980) is now known as the Vroman effect and causes a more elastic or more firmly bound protein layer at the surface. The difference between f response of the harmonics considered may stem from the fact that the penetration depth decreases with the increase in operating frequency of the sensor (Cote et al, 2003;Hieda et al, 2004). Our results indicated that the sensor response to Stage-1 is primarily due to platelet binding to both collagen and to pre-absorbed protein layers, and that the TSM sensor operating at 35 MHz is more sensitive to the molecular interactions such as the Vroman effect occurring in very close proximity to the sensor surface, compared to operating at 5 MHz.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoporous gold is very interesting for application in catalysis [6–7], for sensors [8], for actuators [9–10], and as electrodes for electrochemical supercapacitors [11]. This is due to the unique structural, mechanical and chemical properties of this material [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoporous gold (NPG) has attracted increasing attentions due to its unique 3D bi-continuous ligament-channel structure with large specific surface areas for the applications in catalysis [1][2][3] and sensors [4]. Besides that, it has been also demonstrated that NPG can be used for biomolecules sensing with high sensitivity via surface enhanced Raman spectroscopy (SERS) due to its high surface-to-volume ratio together with its exceptional plasmonic properties [1, 5,6].…”
Section: Introductionmentioning
confidence: 99%